Fodor's 2009 California - Nalepa, Michael; Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to California, with maps and information on hotels and restaurants, shopping and entertainment, and other interesting sites.
"Pullout map inside"--Cover.
Cover title: California 2009.
Includes index.
Maps on endpaper.
Spine title: Fodor's California 2009.
Young Adult
Keywords: California -- Guidebooks; California -- Guidebooks